PENGEMBANGAN MEDIA AUDIO VISUAL BERBANTUAN GOOGLE DRIVE PADA PEMBELAJARAN TEMATIK - Fadilah Azzahra; Damanhuri; Reksa Adya Pribadi; Muhammad Taufik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The goal of this study was to assess the viability of using audio-visual learning media to promote students’ learning, particularly in thematic learning, as well as students’ responses to the media generated by researchers. The research approach was Research and Development (R&D) following the 4D (Four-D) development model of define, design, develop, and disseminate. Based on the opinions of teachers, media professionals, and material experts, the results demonstrated the viability of audio-visual media. Each teacher had an average score of 87.5%, while media specialists received an average score of 92.3% and material experts received an average score of 79.2%. Following that, the students' reactions to the media employed in the learning process were 96.9%. Based on the findings of these investigations, it was concluded that this research created audio-visual media products in the form of learning films in thematic learning for grade V Elementary School using Google Drive. The teacher and media expert validation results fell into the